A Cross Sectional Assessment of Hospital Pharmacist’s Perception towards Online Health Information in Quetta, Pakistan - Akram, Azfar; Iqbal, Qaiser; Haider, Sajjad; Ishaq, Rabia; Saleem, Fahad (Journal of Pharmacy Practice and Community Medicine)
Objectives: The current study aims to assess the perception towards use of online health-related information among hospital pharmacists practicing at public healthcare institutes of Quetta city, Pakistan. Methods: This was a questionnaire based cross sectional survey. Sampling frame of this study was all hospital pharmacists practicing at public hospitals of Quetta city, Pakistan. The data instrument consisted of three sections namely perception towards online health-related information, type of online health-related information used and barriers encountered while retrieving online health-related information. The data was coded and transferred to Statistical Package for Social Science v 20.0 and whereas both descriptive and inferential statistics were used for data elaboration. Results: Out of 116 hospital pharmacists, eight one responded with a response rate of 69.8%. Majority (86.4%) of the respondents agreed that the Internet provides useful and updated health-related information. Nearly 70% of the respondents were also of the opinion that it is their practice to visit an established website. The most sought out information was about drugs followed by general healthcare and disease-related information (92.5%, 74.0% and 61.7% respectively). The main barrier (40, 49.3%) was profusion of health-related information that at times becomes a barrier in obtaining the right information retrieve to scan through from the Internet. Statistical significant differences (p<0.05) were reported among educational status and certain items of the questionnaire whereby postgraduate pharmacists were more in agreement to the statements. Conclusion: It is evident that our respondents are connected to Internet for professional usage and integrate Internet as an adjunct support in their practice. However, certain barriers and limitations were also indentified. For an effective usage of internet based learning, the barriers need to be addressed and facilities should be provided to the hospital pharmacists so that they can utilize an important source of information during their professional practice.
Keywords: Hospital pharmacists; Perception; Online Health Information